2017
DOI: 10.1155/2017/8605313
|View full text |Cite
|
Sign up to set email alerts
|

Adhesive-Enhanced Sternal Closure: Feasibility and Safety of Late Sternal Reentry

Abstract: This clinical case report describes sternal reentry performed years after adhesive-enhanced sternal closure using Kryptonite bone cement. This report provides novel data on the late effects of this innovation. We observed that sternal reentry is feasible and safe. The adhesive did not weaken from biodegradation over a period of several years. There was no evidence of adherence to adjacent soft tissues or other nonbony deep mediastinal structures. Surgeons who receive patients who require redoing cardiac surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The most tried product as an alternative/supportive to steel wires is castor oil-based Kryptonite bone cement. Although many studies have stated that Kryptonite is safe, reliable, effective, and quick, it is no longer available on the surgical market. ,, Another product developed as an alternative/supportive to steel wires is the hyperbranched poly (amino ester)-based nanocomposite adhesive reported by Zhang . Although the adhesive is reported to show good adhesion and mechanical properties, it does not meet the exact results as it has been tested in an ex vivo sternal model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most tried product as an alternative/supportive to steel wires is castor oil-based Kryptonite bone cement. Although many studies have stated that Kryptonite is safe, reliable, effective, and quick, it is no longer available on the surgical market. ,, Another product developed as an alternative/supportive to steel wires is the hyperbranched poly (amino ester)-based nanocomposite adhesive reported by Zhang . Although the adhesive is reported to show good adhesion and mechanical properties, it does not meet the exact results as it has been tested in an ex vivo sternal model.…”
Section: Resultsmentioning
confidence: 99%
“…reported that Kryptonite bone cement, when combined with a standard wire cerclage, increases mechanical strength, prevents sternal dehiscence, reduces postoperative pain, and improves the quality of life after conventional cardiac surgery . In similar studies with Kryptonite, great advantages were also observed compared to steel wires, and it was determined that it prevents major sternal complications. , Kryptonite is a castor oil-based and US Food and Drug Administration (FDA)-approved polymeric bone cement. However, it is no longer available on the surgical market.…”
Section: Introductionmentioning
confidence: 99%
“…Ideal adhesives could either be biologically inert or guide the healing response as with a tissue engineering approach [53]: the same biomechanical design principles apply to minimizing stress concentrations for tissue engineered biomaterials at interfaces between soft and hard tissues. Current adhesive approaches to orthopedic repair primarily use bone cements (e.g., [54]), cyanoacrylate- [55, 56, 57, 58, 59] or methacrylate-based chemistries [60, 61, 62, 63], which may be appropriate for fracture repair but are significantly more stiff than desirable for tendon-to-bone repair. Furthermore, biocompatibility is limited unless all free acrylate moieties are consumed.…”
Section: Discussionmentioning
confidence: 99%
“…Kryptonite™ can bond directly with bone and provides rigid bone fixation and stability which can in turn enhance sternal union and osteosynthesis. It resulted in early recovery after cardiac surgery without any side effects and also reduced the levels of pain marker, IL‐6 81–85 …”
Section: Progress In Enhancing Sternal Healing Controlling Bleedingmentioning
confidence: 99%